The Effect of Learning Using the Structural Analysis Method on Students' Understanding of Poetry in Wasiat Renungan Masa by Maulana Syaikh - Turmuzi, Ahmad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This study investigates the impact of the Structural Analysis Method on students' understanding of the poetry Wasiat Renungan Masa by Maulana Syaikh, addressing a critical gap in effective teaching methods for poetry in secondary education, where students often struggle to grasp the deeper meanings of literary works. The research was conducted with 54 students in class XI Science (IPA) and class XI Social Science (IPS) at MA NW Ar-Rahmaniyah Senyiur, using a quasi-experimental design with a Nonequivalent Control Group to ensure reliable comparisons. The experimental group was taught using the Structural Analysis Method, which focuses on dissecting the structural elements of the poem, while the control group received conventional instruction without emphasis on such analysis. Data were collected through pre-tests and post-tests designed to measure students' understanding of key poetic elements. The collected data were analyzed using parametric statistics, including t-tests, to compare the groups' performance in a statistically rigorous manner. The results show a significant improvement in poetry comprehension for the experimental group, with an average gain score of 19.5, compared to 9.0 in the control group. Statistical analysis using a t-test confirms a significant difference (t-value = 11.54, p < 0.001) between the two groups. The study concludes that the method is highly effective in enhancing poetry understanding and suggests broader applications in literature education, particularly in improving students' ability to analyze and interpret complex texts more effectively.